A Coffee Table Book Project By FTKKP With Sekolah Kebangsaan Gambang Commemorates The Exclusivity Of Herbs In Malaysia - Norasyikin, Ismail (Faculty of Chemical and Process Engineering Technology, 2021)
Separation & Transport Research Cluster, Faculty of Chemical & Process Engineering Technology (FTKKP), Universiti Malaysia Pahang (UMP) to collaborate with Sekolah Kebangsaan Gambang (SKG), Pahang in publishing a Coffee Table Book that commemorates the exclusivity of herbs in Malaysia.